A solid electrolyte with high ionic conductivity and its preparation method
By designing a LiMXCl4 matrix material, a Li3PS4 core-shell structure composite material, and a directional nanowire reinforcement phase, the problems of ionic conductivity, electrochemical window, and mechanical strength of solid electrolytes were solved, enabling the practical application of high-energy-density all-solid-state lithium batteries.
Patent Information
- Application Number
- CN202510751981.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-06
- Publication Date
- 2025-12-02
- Estimated Expiration
- 2045-06-06
AI Technical Summary
Existing solid electrolytes have shortcomings in terms of ionic conductivity, electrochemical window, interfacial compatibility, and mechanical strength, making it difficult to meet the needs of high-energy-density all-solid-state lithium batteries.
A high-ionic-conductivity solid electrolyte was prepared by using LiMXCl4 matrix material and Li3PS4 core-shell structure composite material, combined with directional nanowire reinforcement phase and gradient doping design, and through low-temperature sintering and UV curing casting technology, optimizing the electrochemical window and mechanical properties.
It significantly improves the room temperature lithium-ion conductivity to ≥10 mS/cm, activation energy to ≤0.2eV, expands the electrochemical window to 2.5-4.0V, increases the mechanical strength to ≥100 MPa, suppresses lithium dendrite penetration, and improves the cycle stability and safety of the full cell.
Smart Images

Figure CN120581680B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid electrolytes, specifically to a solid electrolyte with high ionic conductivity and its preparation method. Background Technology
[0002] With the rapid development of all-solid-state lithium batteries, solid electrolytes, as core components, have become key factors restricting battery energy density and safety due to their ionic conductivity, electrochemical stability, and mechanical properties.
[0003] Traditional oxide-based solid electrolytes (such as LLZO) possess high ionic conductivity, but their rigid interfaces have poor compatibility with electrode materials and require high-temperature sintering (>1000℃), resulting in high processing costs. Sulfide electrolytes (such as LGPS) exhibit excellent room-temperature ionic conductivity (>10). -3 While its electrochemical window is relatively narrow (<2.5 V), it is prone to side reactions with high-voltage cathodes, leading to deterioration of cycle performance. Although halide solid electrolytes (such as Li3YCl6) show the potential for a wide electrochemical window, their room temperature conductivity is generally low (usually <1 mS / cm) and their activation energy is high (>0.3 eV), which limits their practical application.
[0004] In existing technologies, regulation is achieved through a single anion (such as Cl). - or F - While it can partially improve the electrochemical stability of halide electrolytes, it is difficult to balance the contradiction between ionic conductivity and voltage window. For example, LiTaCl6-based electrolytes, although capable of passing through Cl... - While the framework achieves high ion mobility, its upper limit of the electrochemical window is less than 3.5 V, making it difficult to adapt to high-nickel cathode materials. Furthermore, in the design of composite electrolytes, the interfacial compatibility issue of the core-shell structure has not been effectively resolved. Active cores such as Li3TiCl6 are prone to interfacial reactions with sulfide shells (such as Li3PS4), leading to obstructed ion transport pathways. Simultaneously, traditional sintering processes easily induce increased grain boundary impedance, and the lack of directional arrangement design of reinforcing phases results in insufficient mechanical strength of the electrolyte membrane (typically <50 MPa), making it difficult to suppress lithium dendrite penetration. Summary of the Invention
[0005] Based on this, the purpose of this invention is to provide a high ionic conductivity solid electrolyte and its preparation method, so as to solve the technical problems of the shortcomings of existing solid electrolytes in terms of ionic conductivity, electrochemical window, interfacial compatibility and mechanical strength.
[0006] In view of the above-mentioned technical problems, this application provides a solid electrolyte with high ionic conductivity and a method for preparing the same.
[0007] The first aspect of this application provides a high-ionic-conductivity solid electrolyte, comprising the following components:
[0008] Matrix material: A halide superionic conductor with a LiMXCl4 structure, wherein M is selected from at least one of Ta, Nb, and Hf, X is F, and the general chemical formula is LiM 1-a X 1-6 Cl4, where a = 0.1-0.3, and the electrochemical window is adjusted to 2.5-4.0 V by fluorine-chlorine mixed anion substitution;
[0009] Second-phase material: core-shell structured composite, with a core of Li3TiCl6 and a shell of Li3PS4 interface layer, and a core-shell mass ratio of 1:0.1-0.5;
[0010] Sintering aid: A composite of Li3BO3 and LiF, with a total content of 1-5% of the matrix material mass;
[0011] Directed nanowire reinforcing phase: selected from MgAl2O4:Mn 4+ Or SiO2, with a diameter of 10-30 nm, a length of 1-3 μm, and a content of 0.5-3 wt%;
[0012] The electrolyte has a lithium-ion conductivity ≥10 mS / cm at room temperature, and achieves an ion migration path with an activation energy ≤0.2eV through the coordinated tilting of MO2Cl4 octahedra driven by the soft cradle effect.
[0013] Furthermore, Zr is introduced into the LiMXCl4 matrix material. 4+ or Sn 2+ Doping, with a doping amount of 5-15% of the molar number of M, is used to control the free volume between MO2Cl4 chains, so that the octahedral tilt angle is controlled within the range of 20°-30°, and the difference in ionic conductivity distribution along the thickness direction is ≤10% through gradient doping.
[0014] Furthermore, in the core-shell composite, the Li3TiCl6 core has a particle size of 50-200 nm, the Li3PS4 interface layer has a thickness of 2-5 nm, and the surface of Li3TiCl6 is modified with a silane coupling agent to enhance its interfacial compatibility with the matrix material.
[0015] A second aspect of this application provides a method for preparing the above-mentioned solid electrolyte, comprising the following steps:
[0016] Precursor preparation: LiMXCl4 precursor was synthesized by mechanochemical method, with ball milling speed controlled at 500-800 rpm and ball-to-material ratio at 20:1, and pre-sintered in argon at 400-600℃ to form MO2Cl4 chain structure.
[0017] Core-shell composite coating: Li3PS4 interface layer is coated on the surface of Li3TiCl6 by atomic layer deposition at a deposition temperature of 200-300℃ and a cycle count of 50-100.
[0018] Casting film formation: The matrix material, core-shell composite, sintering aid and oriented nanowires are mixed, and a PVDF solution containing photoinitiator is added. The mixture is then cast into a film by UV curing. The curing energy density is 50-100mW / cm².
[0019] Pressure sintering: Two-stage pressure sintering is adopted: first, the temperature is raised to 800℃ at 5℃ / min under axial pressure of 5-10 MPa and held for 2h, and then the temperature is lowered to 300℃ at 2℃ / min under lateral constraint pressure of 0.5-1 MPa.
[0020] Interface modification: A Li3PO4-LiF composite layer with a thickness of 100-200 nm is spin-coated on the positive electrode side, and an anion-derived SEI film containing LiF and Li3N components is generated on the negative electrode side by chemical vapor deposition with a film thickness ≤50 nm.
[0021] Furthermore, during the UV curing process of the casting film, a 1-3T magnetic field is applied simultaneously to orient the nanowires along the direction of the magnetic field, and the curing time is adjusted to 10-30 min by real-time fluorescence monitoring of the nanowire arrangement density.
[0022] In summary, the present invention has the following main beneficial effects:
[0023] This invention significantly improves the ion conductivity of solid-state electrolytes through the regulation of fluorine-chlorine mixed anions and the synergistic tilting mechanism of MO2Cl4 octahedrons. The room-temperature lithium-ion conductivity reaches ≥10 mS / cm, and the activation energy is ≤0.2 eV, which is superior to traditional halide electrolytes. Simultaneously, through Zr... 4+ / Sn 2+ Gradient doping optimizes the free volume between chains, and combined with core-shell structured composites (Li3TiCl6; Li3PS4) and silane coupling agent modification, effectively broadening the electrochemical window to 2.5-4.0V, suppressing interfacial side reactions, and adapting to high-voltage cathode materials.
[0024] The present invention relates to a directional nanowire-reinforced phase (such as MgAl2O4:Mn). 4+The synergistic effect of the two-stage pressure sintering process and the electrolyte's flexural strength is increased to ≥100 MPa, significantly suppressing lithium dendrite penetration. The fabrication process employs low-temperature pre-sintering (≤600℃) and UV curing casting technology, simplifying the process and reducing costs. Furthermore, the magnetic field-oriented arrangement of nanowires and interface modification (Li3PO4-LiF composite layer, anion-derived SEI film) further enhance the cycle stability and safety of the full battery, providing a reliable solution for the practical application of high-energy-density solid-state lithium batteries. Attached Figure Description
[0025] Figure 1 This is a flowchart illustrating the preparation process of the high ionic conductivity solid electrolyte of the present invention. Detailed Implementation
[0026] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0027] Soft cradle effect: Through the coordinated tilting and dynamic reconstruction of MO2Cl4 octahedra, low-barrier ion migration channels are formed, with activation energy ≤0.2eV.
[0028] Gradient doping: Zr along the thickness direction of the electrolyte film 4+ or Sn 2+ The doping concentration decreases linearly from the surface to the bottom layer (e.g., 15% → 5%) to optimize the free volume distribution between chains.
[0029] Two-stage pressure sintering: The first stage involves high-temperature sintering under axial pressure to eliminate grain boundary porosity, and the second stage involves slow cooling under transverse confinement pressure to reduce residual stress and improve mechanical strength.
[0030] Core-shell interface compatibility: The surface of Li3TiCl6 is modified with a silane coupling agent (such as KH550) to form a chemically bonded interface, which inhibits the side reactions between Li3PS4 and the core.
[0031] The embodiments of the present invention will now be described.
[0032] Example 1: Matrix material optimization (fluorine-chlorine mixed anion regulation)
[0033] Components and proportions:
[0034] Matrix material: LiTa 0.8 Zr 0.2 OCl4 (a=0.2, Zr doping 10%), Cl:F=3:1.
[0035] Core-shell composite: Li3TiCl6 (particle size 100 nm) / Li3PS4 (thickness 3 nm), core-shell mass ratio 1:0.3.
[0036] Sintering aid: Li3BO3-LiF composite (mass ratio 2:1), total content 3%.
[0037] Directed nanowires: MgAl2O4:Mn 4+ (Diameter 20nm, length 2μm), content 2wt%.
[0038] Preparation steps:
[0039] Precursor preparation: ball milling (600 rpm, 6 h) followed by pre-sintering (500 °C, 4 h) to form a Ta-O-Cl chain structure.
[0040] Core-shell coating: ALD deposition of Li3PS4 (250℃, 80 cycles), surface modified with KH550.
[0041] Casting film: UV curing (80mW / cm², 2T magnetic field, 20min), film thickness 50μm.
[0042] Pressure sintering: axial 8MPa / 800℃ → transverse 0.8MPa / 300℃.
[0043] Interface modification: positive electrode side Li3PO4-LiF (150nm), negative electrode side LiF-Li3N SEI film (40nm).
[0044] Performance testing:
[0045] Ionic conductivity: 12.5 mS / cm (25℃), activation energy: 0.18 eV;
[0046] Bending strength: 110MPa (three-point bending method);
[0047] Electrochemical window: 2.5-4.0V (LSV test);
[0048] Cyclic stability: 92% capacity retention after 500 cycles at 0.5C.
[0049] Example 2: Synergistic enhancement of gradient doping and oriented nanowires
[0050] Component adjustment:
[0051] Matrix material: LiNb 0.85 Sn 0.15 FCl4 (Sn) 2+ Gradient doping: 15% on the surface layer → 5% on the bottom layer.
[0052] Nanowire type: SiO2 nanowires (diameter 25nm, length 1.5μm), content 1.5wt%.
[0053] Preparation differences:
[0054] Sn is produced by layered pressing technology after ball milling. 2+ Concentration gradient distribution.
[0055] The magnetic field strength was adjusted to 1.5T, and the curing time was 15 minutes.
[0056] Test results:
[0057] Differences in ionic conductivity distribution: 7.5% difference in the thickness direction;
[0058] Flexural strength: 105 MPa;
[0059] Interface impedance: 25 Ω·cm² (EIS test), 15% lower than Example 1.
[0060] Example 3: Core-shell mass ratio optimization
[0061] Component adjustment:
[0062] Core-shell composite: Li3TiCl6 (particle size 150 nm) / Li3PS4 (thickness 5 nm), core-shell mass ratio 1:0.5.
[0063] Test results:
[0064] Ionic conductivity: 11.2 mS / cm;
[0065] Electrochemical window: 2.5-4.0V;
[0066] Suppression of interfacial side reactions: XPS analysis showed that the sulfide shell effectively blocked the reaction between Li3TiCl6 and the matrix.
[0067] Comparative Example 1: Traditional halide electrolytes (without core-shell structure)
[0068] Composition: Li3YCl6 matrix, core-shell-free composite and nanowires.
[0069] performance:
[0070] Ionic conductivity: 0.8 mS / cm;
[0071] Activation energy: 0.35 eV;
[0072] Flexural strength: 45 MPa;
[0073] Electrochemical window: 2.0-3.2V.
[0074] Comparative Example 2: No Gradient Doping
[0075] Component: LiTa 0.8 Zr 0.2O Cl4 (uniformly doped with Zr).
[0076] result:
[0077] Difference in ionic conductivity distribution: 18%;
[0078] Bending strength: 90MPa (fracture caused by grain boundary stress concentration).
[0079] Comparative Example 3: Single Anion System (No Fluorine Doping)
[0080] Composition: LiTaCl6 matrix (without F doping).
[0081] performance:
[0082] Electrochemical window: 2.8-3.5V;
[0083] Ionic conductivity: 8.5 mS / cm;
[0084] Cyclic stability: 78% capacity retention after 500 cycles.
[0085] Comprehensive Analysis Table of Experimental Data
[0086] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Ionic conductivity (mS / cm) 12.5 11.8 11.2 0.8 9.5 8.5 Activation energy (eV) 0.18 0.19 0.20 0.35 0.25 0.28 Flexural strength (MPa) 110 105 100 45 90 85 Electrochemical window (V) 2.5-4.0 2.5-4.0 2.5-4.0 2.0-3.2 2.5-3.8 2.8-3.5 Cycle retention rate (%) 92 94 90 65 85 78
[0087] Ball milling time and particle size distribution:
[0088] When ball-milled for 6 hours, the precursor particle size D 50 =1.2μm, uniformly distributed;
[0089] When it is below 4 hours, D 50 >2μm, which leads to an increase in grain boundary impedance after sintering.
[0090] ALD loop count and interface layer performance:
[0091] After 80 cycles, the Li3PS4 layer is continuous and dense, with the lowest interface impedance (25Ω·cm²).
[0092] When the number of cycles is less than 50, there are pores in the interface layer and the impedance is greater than 50 Ω·cm².
[0093] Magnetic field strength and nanowire arrangement:
[0094] Under a 2T magnetic field, the nanowire orientation density reaches 90%, and the bending strength is increased by 30%.
[0095] In the absence of a magnetic field, the nanowires are randomly distributed and have an intensity of only 70 MPa.
[0096] Example 1 performs best in the following aspects:
[0097] Ionic conductivity (12.5 mS / cm): Fluorine-chlorine mixed anions synergistically tilt the MO2Cl4 octahedron, reducing the activation energy to 0.18 eV;
[0098] Mechanical strength (110MPa): MgAl2O4:Mn 4 Synergistic effect of nanowire orientation and two-stage sintering;
[0099] Electrochemical stability (2.5-4.0V): Core-shell structured complex and gradient doping effectively suppress interfacial side reactions.
[0100] Example 2 has advantages in terms of interface impedance and cycle stability, making it suitable for high-rate applications.
[0101] Example 3 further optimizes interface protection by increasing the core-shell ratio, but sacrifices some ionic conductivity.
[0102] This invention significantly improves the overall performance of solid-state electrolytes through fluorine-chlorine mixed anion regulation, gradient doping design, core-shell structure interface optimization, and directional nanowire reinforcement. Example data show that its ionic conductivity, mechanical strength, and cycle stability are superior to traditional methods, making it particularly suitable for high-voltage (≥4.0V) cathode systems, providing a reliable technical path for the industrialization of all-solid-state lithium batteries.
[0103] Although embodiments of the present invention have been shown and described, these specific embodiments are merely explanations of the invention and are not intended to limit it. The specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. After reading this specification, those skilled in the art may make modifications, substitutions, and variations to the embodiments as needed without departing from the principles and spirit of the invention, but such modifications, substitutions, and variations are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A solid electrolyte with high ionic conductivity, characterized in that: It contains the following components: Matrix material: A halide superionic conductor with a LiMXCl4 structure, wherein M is selected from at least one of Ta, Nb, and Hf, X is F, and the general chemical formula is LiM 1-a X 1-6 Cl4, where a = 0.1-0.3, and the electrochemical window is adjusted to 2.5-4.0 V by fluorine-chlorine mixed anion substitution; Second-phase material: core-shell structured composite, with a core of Li3TiCl6 and a shell of Li3PS4 interface layer, and a core-shell mass ratio of 1:0.1-0.5; Sintering aid: A composite of Li3BO3 and LiF, with a total content of 1-5% of the matrix material mass; The electrolyte has a lithium-ion conductivity ≥10 mS / cm at room temperature, and achieves an ion migration path with an activation energy ≤0.2eV through the coordinated tilting of MO2Cl4 octahedra driven by the soft cradle effect. Zr was introduced into the LiMXCl4 matrix material. 4+ or Sn 2+ Doping, with a doping amount of 5-15% of the molar number of M, is used to control the free volume between MO2Cl4 chains, so that the octahedral tilt angle is controlled within the range of 20°-30°, and the difference in ionic conductivity distribution along the thickness direction is ≤10% through gradient doping.
2. The high ionic conductivity solid electrolyte according to claim 1, characterized in that: In the core-shell composite, the Li3TiCl6 core has a particle size of 50-200 nm, the Li3PS4 interface layer has a thickness of 2-5 nm, and the surface of Li3TiCl6 is modified with a silane coupling agent to enhance its interfacial compatibility with the matrix material.
3. The high ionic conductivity solid electrolyte according to claim 1, characterized in that: It also includes 0.5-3 wt% of a oriented nanowire reinforcing phase, wherein the nanowires are selected from MgAl2O4:Mn 4+ Alternatively, SiO2, with a diameter of 10-30 nm and a length of 1-3 μm, is used, and the electrolyte is oriented along the film plane through a UV-curing assisted casting process, thereby increasing the flexural strength of the electrolyte to ≥100 MPa.
4. A method for preparing a solid electrolyte as described in any one of claims 1-3, characterized in that... Includes the following steps: S1: The LiMXCl4 precursor was synthesized by mechanochemical method, with ball milling speed controlled at 500-800 rpm and ball-to-material ratio at 20:1, and pre-sintered in argon at 400-600℃ to form a MO2Cl4 chain structure. S2: A Li3PS4 interface layer is deposited on the surface of Li3TiCl6 by atomic layer deposition at a deposition temperature of 200-300℃ and a cycle count of 50-100. S3: Mix the matrix material, core-shell composite, sintering aid and oriented nanowires, add PVDF solution containing photoinitiator, and cast into a film by UV curing, with a curing energy density of 50-100mW / cm². S4: Two-stage pressure sintering is adopted: first, the temperature is raised to 800℃ at 5℃ / min under axial pressure of 5-10 MPa and held for 2h, and then the temperature is lowered to 300℃ at 2℃ / min under lateral constraint pressure of 0.5-1 MPa.
5. The preparation method according to claim 4, characterized in that: In step S3, a 1-3T magnetic field is applied simultaneously during UV curing to orient the nanowires along the direction of the magnetic field. The curing time is adjusted to 10-30 min by monitoring the nanowire density with real-time fluorescence.
6. The preparation method according to claim 4, characterized in that: After sintering in step S4, the electrolyte sheet undergoes interface modification, including: A Li3PO4-LiF composite layer with a thickness of 100-200 nm is spun onto the positive electrode side. An anion-derived SEI film containing LiF and Li3N components was generated on the negative electrode side by chemical vapor deposition, with a film thickness ≤50nm.
Citation Information
Patent Citations
Solid electrolyte and preparation method thereof, and lithium ion battery
CN109428115A
Halide solid electrolyte, preparation method thereof and all-solid-state lithium ion battery
CN118589029A